PERCEPTIONS OF HEALTH CARE PROFESSIONALS ON THE SCOPE AND ROLE OF FAMILY MEDICINE: A SURVEY ON HEALTHCARE SYSTEM OF PAKISTAN - NAEEM, N; IJAZ, S; MAJID, Z; NAZ, H; LODHI, N; MANSOOR, A (Biological and Clinical Sciences Research Journal, 2023)
This study aimed to explore healthcare professionals’ perceptions regarding the scope and role of family medicine in the healthcare system of Pakistan. A cross-sectional survey was conducted among undergraduate students (n=170) and professional doctors (n=130) in Pakistan. Participants were recruited through convenience sampling. Data were collected using a self-administered questionnaire that assessed knowledge, attitudes, and career choices related to family medicine. The findings revealed that many participants demonstrated knowledge of family medicine as a specialty. Both undergraduate students and professional doctors expressed positive attitudes toward family medicine as a career choice. However, a higher percentage of professional doctors had knowledge of family medicine compared to undergraduate students. The study also highlighted the potential impact of creating specialist posts in family medicine in encouraging healthcare professionals to choose it as a career. The study’s results indicate a growing recognition and acceptance of family medicine as a vital component of the healthcare system in Pakistan. Efforts should be made to enhance awareness and knowledge of family medicine among undergraduate students, promote interprofessional collaboration, and support evidence-based policymaking to strengthen the role of family medicine. These measures can improve healthcare access, quality, and outcomes in Pakistan.